Does Sleep Help Prevent Forgetting Rewarded Memory Representations in Children and Adults? - Prehn-Kristensen, Alexander; Böhmig, Annie; Schult, Juliane; Pedersen, Anya; Wiesner, Christian D.; Baving, Lioba (Frontiers in Psychology, 2018)
Sleep fosters the consolidation of rewarded memory representations in adults. However, sleep and its memory-supporting functions change through healthy development, and it is unclear whether sleep benefits the consolidation of rewarded memory representations in children as it does in adults. Based on previous findings, we expected sleep to benefit the consolidation of rewarded memory representations in children more than it does in adults. For that reason, 16 children (7-11 yrs) and 20 adults (21-29 yrs) participated in this experiment. During the encoding session, participants were asked to learn the location of 18 object pairs. Thereafter, one half of the object locations were allocated to a high-rewarded condition and the other half to a low-rewarded condition. In the sleep condition, the encoding session took place in the evening (for children 7-8 p.m., for adults 8-9 p.m.). After a fixed retention interval of 12 hours the retrieval session was conducted the next morning (for children 7-8 a.m., for adults 8-9 a.m.). In the wake condition, the time schedule was the same but reversed: the encoding session started in the morning (for children 7-8 a.m., for adults 8-9 a.m.), and retrieval took place in the evening (for children 7-8 p.m., for adults 8-9 p.m.). Sleep/wake had no impact on the memory performance regarding the low-rewarded memory items. In contrast, wakefulness in comparison to sleep reduced the memory performance on high-rewarded memory items. The interaction between sleep/wake and the degree of reward on memory performance was only significant in children. These results show that 12h of wakefulness can deteriorate the memory performance for high-rewarded representations, whereas sleep can prevent the forgetting of these rewarded representations. It is discussed whether ontogenetic changes in sleep may play a role in conserving relevant but fragile memory representation.